Impact of COAPT trial exclusion criteria in real-world patients undergoing transcatheter mitral valve repair. (1st October 2020) - Iliadis, Christos; Metze, Clemens; Körber, Maria Isabel; Baldus, Stephan; Pfister, Roman
Abstract: Background: The generalizability of the COAPT trial results on the benefit of TMVR in patients with secondary mitral regurgitation is unclear. Methods: Functional and long-term clinical outcome were examined in 122 consecutive patients with secondary mitral regurgitation and reduced ejection fraction undergoing TMVR. "COAPT-like" patients were defined according to principal COAPT inclusion/exclusion criteria if all of the following was fulfilled: symptomatic mitral regurgitation grade 3+ or more according to American guidelines; left ventricular ejection fraction ≥ 20%, left ventricular end-systolic dimension ≤ 70 mm, estimated pulmonary artery systolic pressure ≤ 70 mmHg, mitral valve orifice area ≥ 4 cm 2, no prior mitral valve procedure, no right sided congestive heart failure, no COPD requiring home oxygen therapy and NYHA class less than IVb. Results: 51% of 122 patients (mean age 74 ± 10 years, 76% male) showed COAPT-like characteristics. COAPT-like patients showed a significantly lower hazard for the composite endpoint of mortality and heart failure hospitalization (HR 0.51, 95%CI 0.30–0.89, p  = .017) during a mean follow-up of 16 ± 6 months, with an estimated 1-year event rate of 20% vs 43%, respectively. The improvement in functional outcomes 6 min walking distance (76 ± 136 m vs. 31 ± 90 m), Minnesota Living with Heart Failure Questionnaire (−6 ± 19 vs. −10 ± 23) and Short Form 36 physical component score (3.8 ± 10 vs. 5.5 ± 11) was similar in COAPT-like and the other patients. Conclusion: In this first real world cohort half of the patients undergoing TMVR showed COAPT-like characteristics and these patients showed a substantially better clinical outcome. The mid-term functional benefit was similar in COAPT-like and other patients. Highlights: Trials of TMVR in patients with secondary mitral regurgitation are controversial. The COAPT trial showed a substantial benefit in a highly selected study population. COAPT-like patients represent approximately half of TMVR patients in a real-world cohort. Non COAPT-like patients had a substantially worse long-term clinical outcome. Functional benefit was similar in COAPT-like and non COAPT-like patients.